A multisite randomized controlled trial of an early palliative care intervention in children with advanced cancer: The PediQUEST Response Study Protocol - Dussel, Veronica; Orellana, Liliana; Holder, Rachel; Porth, Rachel; Avery, Madeline; Wolfe, Joanne (PLOS ONE, 2022)
Background The Pediatric Quality of Life and Evaluation of Symptoms Technology Response to Pediatric Oncology Symptom Experience (PQ-Response) intervention aims to integrate specialized pediatric palliative care into the routine care of children, adolescents, and young adults (AYAs) with advanced cancer. Aims To evaluate whether PQ-Response, compared to usual care, improves patient’s health related quality of life (HRQoL) and symptom burden (aim 1), parent psychological distress and symptom-related stress (aim 2), and family and symptom treatment activation (aim 3). Design Multisite, randomized (1:1), controlled, un-blinded, effectiveness trial comparing PediQUEST Response (intervention) vs usual cancer care (control). Setting Five US large, tertiary level pediatric cancer centers. Participants Children (≥2 years old)/AYAs who receive care at any of the participating sites because of advanced cancer or any progressive/recurrent solid or brain tumor and are palliative care “naïve.” Target: 200 enrolled patient-parent dyads (minimum goal: 136 dyads randomized, N = 68/arm). Interventions PediQUEST Response: combines patient-mediated activation (weekly feedback of patient- and parent-reported symptoms and HRQoL to families and providers using the PediQUEST web system) with integration of the palliative care team. Usual Cancer Care: participants receive usual care, which can include palliative care consultation, and use PediQUEST web to answer surveys, with no feedback. Methods Following enrollment, patients (if ≥5 years) and one parent receive weekly PediQUEST-Surveys assessing HRQoL (Pediatric Quality of Life Inventory 4.0) and symptom burden (PediQUEST-Memorial Symptom Assessment Scale). After a 2-week run-in period, dyads who answer ≥2 PediQUEST surveys per participant (responders), are randomized (concealed allocation) and followed up for 16-weeks. Parents answer six additional surveys (parent outcomes). Outcomes Primary: mean patient HRQoL score over 16-weeks as reported by a) the parent; and b) the patient if ≥5 years-old. Secondary: patient’s symptom burden; parent’s anxiety, depressive symptoms, symptom-related stress; family activation; and symptom treatment activation. Trial registration ClinicalTrials.gov (NCT03408314) 1/24/18. https://clinicaltrials.gov/ct2/show/NCT03408314.